New Plasma Separation Glucose Oxidase-based Glucometer in Monitoring of Blood With Different PO2 Levels - Ming-Sheng Lee; Lon-Yen Tsao; Yu-Ching Tseng; Shiu-Jung Tsai; Mei-Li Tsai; Tony Huang; Han-Yao Chiu (Pediatrics and Neonatology)
The PalmLab glucometer is a newly designed plasma separation glucose oxidase (GO)-based glucometer. Past studies have shown that the accuracy of GO-based glucometers is compromised when measurements are taken in patients with high PO2 levels. We performed a two-arm study comparing the fitness of the PalmLab blood glucometer with that of a standard glucose analyzer in monitoring blood glucose levels in pediatric patients, especially when arterial partial pressure of oxygen (PO2) was high. Methods: In the first arm of the study, arterial blood samples from pediatric patients were measured by the PalmLab blood glucometer and the YSI 2302 Plus Glucose/Lactate analyzer. In the second arm of the study, venous blood samples from adult volunteers were spiked with glucose water to prepare three different levels of glucose (65, 150, and 300 mg/dL) and then oxygenated to six levels of PO2 (range, 40–400 mmHg). The biases of the PalmLab glucometer were calculated. Results: A total of 162 samples were collected in the first arm of the study. Results of linear regression showed that the coefficient of determination (R2) between PalmLab glucometer and standard glucose analyzer was 0.9864. Error grid analysis revealed that all the results were within Zone A (clinically accurate estimate zone). The biases between the two systems were low at different PO2 levels. In the second arm of the study, the results were also unaffected by changes in PO2. Conclusion: The PalmLab glucometer provides accurate results in samples with high PO2 and is suitable for measuring arterial glucose levels in pediatric patients.